Estimulación temprana y su incidencia en el desarrollo del lenguaje en niños de Educación Inicial I - Arriaga Quiñonez, Miren Esther (2024)
The research addresses the lack of early stimulation in the language development of children in Initial Education in the "Urdaneta" Educational Unit during the period from October 2023 to March 2024. A notable difficulty is observed in linguistic development due to the lack prioritization of various physical and mental abilities and skills in children. The general objective is to evaluate the influence of early stimulation on language development in these children. The methodological design adopted corresponds to a feasible project, using documentary, field, and descriptive research. The study subjects are teachers and children, using research techniques such as interviews and observations, and tools such as questionnaires and observation sheets. It is based on theories such as early stimulation, aimed at strengthening cognitive, socio-affective, linguistic, and psychomotor abilities. The importance of early stimulation in linguistic development is analyzed to improve children's verbal structure and fluency, promoting communication and socialization with their peers and environment. The results indicate that 67% of teachers carry out early stimulation activities frequently, while 33% do not. Regarding the linguistic development of children, 50% are at a normal level, 33% at an excellent level and 17% at a low level. It is concluded that early stimulation favors the desire to learn in children, highlighting the importance of teachers using methodologies that promote their comprehensive development.